Validasi Metode Analisis KCKT untuk Penetapan Kadar Parasetamol dalam Sediaan Tablet Generik dan Bermerek - Harfiansyah, M. Deddy; Purba, Gratia Apulina Cindylawsa; Fitria, Fitria; Rambe , Ummi Khairani; Amar , Ageng Azhar (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Paracetamol is one of the most widely used analgesic and antipyretic drugs, and quality control of its dosage forms is crucial to ensure therapeutic effectiveness. Objective: This study aimed to validate a simple, rapid, and reliable High-Performance Liquid Chromatography (HPLC) method for the determination of paracetamol content in generic and branded tablet formulations. Methods: The chromatographic analysis was performed on a C18 column using a mobile phase of distilled water and methanol (3:1, v/v) with a flow rate of 1.0 mL.min–1, injection volume of 20 µL, and detection wavelength at 243 nm. Validation parameters including system suitability, linearity, accuracy, precision, limit of detection (LOD), and limit of quantification (LOQ) were evaluated according to pharmacopeial guidelines. Results: The method demonstrated excellent linearity over the range of 8–12 µg.mL–1 (r = 0.9998), with LOD and LOQ values of 0.13 µg.mL–1 and 0.40 µg.mL–1, respectively. Accuracy values were 99.00% for generic and 98.86% for branded tablets, while precision showed %RSD of 0.53% and 0.68%. The paracetamol content was 101.47% and 100.20% for generic and branded formulations, respectively, meeting pharmacopeial standards (90–110%). Conclusion: The validated HPLC method proved to be accurate, precise, and sensitive for the quantitative determination of paracetamol in tablet dosage forms. This method is suitable for routine quality control and can be extended for stability or pharmacokinetic studies.